Postur Kifosis Berhubungan Dengan Gangguan Keseimbangan Postural Lanjut Usia Di Jebres Surakarta - Mutnawasitoh, Asita Rohmah; Susilowati, Tri; Ramadhani, Alinda Nur (Universitas Tribhuwana Tunggadewi, 2024)
The aging process in the elderly population can lead to changes in body posture, often resulting in kyphosis, which exacerbates postural balance disorders. This study aims to determine the relationship between kyphosis posture incidence and postural balance disorders among the elderly in Jebres, Surakarta. The research design employed was an observational analytic correlation with a cross-sectional design, utilizing purposive sampling techniques. The independent variable was kyphosis, while the dependent variable was balance disorders. The instruments used included the Unteberger test for assessing balance and the Occiput-to-Wall distance test for measuring kyphosis. Results from the study revealed that out of 67 respondents from a total population of 75 elderly individuals, 30 (44.77%) experienced kyphosis, with 23 (34.32%) presenting hyper kyphosis. Additionally, 53 (79.10%) respondents exhibited balance disorders, while 14 (20.89%) did not have kyphosis or balance disorders. Bivariate analysis using the Spearman rho test demonstrated a significant correlation between Balance Disorders and Kyphosis Posture, with a Sig (2-tailed) value of 0.001 and a correlation coefficient of 0.759. The relationship between these two variables was found to be unidirectional, indicating a significant association between the incidence of kyphosis posture and postural balance disorders in the elderly in Jebres, Surakarta. For future research, it is recommended to further explore the specific magnitude of kyphosis angles and their impact on postural balance disturbances